Kontribusi Kepala Sekolah Berdasarkan Ketidaksesuain Kualifikasi Guru Untuk Meningkatkan Kualitas Sekolah - Nova Syafira Ariyanti; Ahmad Supriyanto; Agus Timan (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2019)
The aim of this study was to find (1) constraints in improving the quality of schools, (2) the strategy of principals to improve school quality, and (3) the efforts of principals to maintain school quality strategies. This study used a qualitative approach, with the study design of the case study. The place of this study was at the SD Islam Terpadu Robbani Singosari. The technique of collecting data is in-depth interviews and documentation. Analysis of the data obtained results in findings that are in accordance with the problems being faced by the school. The results of the study are (1) constraints to improving the quality of the school, namely the teacher's educational background that is not in accordance with the required qualifications, (2) the principal's strategy to improve the quality of the school includes participating in education seminars and requiring teachers not to qualify again 3) the efforts of the principal to maintain the school quality strategy including providing financial incentives and forming teacher work teams to improve their competence in teaching.